How do we teach safety and sustainability on the roads? Traffic education in 4th grade primary schools in Czechia through the eyes of teachers - Drimlova, Elisabeta; Sucha, Matus (Transactions on Transport Sciences, 2025)
Transport education (TE) is an indispensable part of basic education. It aims to improve road safety and promote healthy lifestyles and environmental sustainability. Using an online questionnaire, we mapped what TE looks like in 4th grade primary schools in Czechia. We received 644 responses from primary school teachers. According to their reports, the practical part of TE is mainly implemented in traffic playgrounds (86%). Schools also implement TE through lectures/lectures with outsiders, e.g. police officers (38%) and organize TE project days (30%). The emphasis on safe behaviour of pupils in traffic is evident in the TE. We recommend more intensive integration of environmental and lifestyle topics and experiential learning, as well as further research on the effectiveness of TE to determine students' actual skills and knowledge.